The far distant city of Paris and someone called Haussmann (Dialogos, 2016)
Discussion on Large Urban Projects. They involve conflicting agents and are subjected to analysis beyond projectual scrutinity. Paper prioritizes the understanding of a selection of printed media contemporaneous to Haussmann´s works in Paris, and is based on three assumptions: criticism observed in the past repeats in contemporary cities; debates, there and now, do not allow for nuances; analysis of the distant observer prevails praise; analysis of someone closer to it is full of harsh criticism. Material used was a selection of The New York Times discussing works of the modernization of Paris under the responsibility of Haussmann. The discussion and conclusion are based on this material and reiterate assumptions adopted.